Illusionism as an investigative artistic practice - Nigro, Miguel Ángel (Universidad Nacional del Litoral, 2021)
This article is part of an ongoing doctoral research whose subject is the object in illusionism. The things involved in magic are the material agents of deception that complement the illusionist’s prominence. The function of objects should be thought of with a previous analysis focused on the strategies that the artist displays in front of productive difficulties. Illusionism is a practice to be link, it has a strong tradition that relies on more or less systematized processes to produce acts, routines or games. It is appropriate to reflect on the nature of the different stages of production, oriented on achieving a spectacular end: the inexplicable. Magicians select their games with a sensitive intuition and they integrate them into the present with a contemporary sense. I analyze which elements remain invariable from the description of each productive phase, how theoretical models are applied or generated, what instabilities a game undergoes in its development and how it is positioned in the face of a constantly expanding theatrical reality. The analysis articulates the specific bibliography and the related fields of knowledge with interviews of active illusionists. My personal experience in scenography, theater of objects and illusionism is transformed into a methodological instrument.